A Cross Sectional Study on Smartphone Addiction among Students in Ayapakkam, Thiruvallur District, Tamil Nadu, 2018 (Indian Journal of Public Health Research & Development, 2020)
Background: India stands second for Smartphone usage in the world according to “global market” report.Smartphone addiction affects the younger generations to a greater extent. The objectives of the study was toestimate the proportion of students of age 18–24 years who were addictive to their Smartphone, to estimatethe average time spent by them, to find the main reasons for usage and also to find the association betweenSmartphone usages and sleep quality of the students.Method: A cross sectional community based study was done in Ayapakkam, Thiruvallur district, TamilNadu. Two stage cluster sampling methodology was employed for selecting a random sample of 139students. In the first stage 4 clusters were selected based on the more populous clusters and in the secondstage a minimum of 35 students were interviewed from each of the selected cluster. Smartphone AddictionScale (SAS) and Pittsburgh Sleep Quality Index(PSQI) were the tools used for assessing the association ofSmartphone addiction and sleep quality of the students. Data was collected using tablet and Epicollect 5 webapplication.Descriptive statistics, Chi-Square for association and t-test to determine whether there exists significantdifference between the means of two groups was assessed.Results: The proportion of students who were addict to their Smartphone was 52.7% and among them itwas more in males (66.2%). On an average 6.42 hours/day was spent on their Smartphone. The major reasonbehind using their Smartphone was for communication (5.03 hours/day). The association between SAS andPSQI were found to be highly significant (?2 = 11.035, p-value < 0.01).Conclusions: It is an alarming sign that students are prone to addiction to Smartphone. The youngergeneration must be brought awareness about their Smartphone addiction and heath impact they are prone indue course of time.
Keywords: Smartphone addiction, Sleep quality, Students